The Relationship between Body Mass Index, Stress Levels, Physical Activity, and the Fitness Level of Polri Members of the Central Java Regional Police - Rudi Irawan; Agung Wahyudi; Rumini Rumini (Journal of Physical Education and Sports, 2026)
Physical Fitness is an important component of physical condition for police officers, including detectives, to ensure they remain ready to carry out their duties. This study aims to determine the relationship between Body Mass Index, Stress Level, Physical Activity Levels, and the Fitness Level of Police Officers in the Central Java Regional Police. This study used a quantitative method with a cross-sectional approach. The population in this study was 2,799 police officers at the Central Java Regional Police Headquarters. The sampling technique used the systematic sampling, resulting in a sample of 140 police officers. The instruments used consisted of BMI (Body Mass Index), GPA-Q (physical activity), PSQ-Op (stress level), and the National Police Physical Fitness Test. Data analysis techniques in this study included descriptive statistics, normality tests, linearity tests, multivariate tests, simple correlation tests, and multiple regression tests. The analysis was conducted using SPSS version 22. The results of the study showed that partially: (1) body mass index contributed 47% with a significant value of p = 0.00; (2) stress levels contributed 36% with a significant value of p = 0.001; and (3) physical activity contributed 17% with a significant value of p = 0.014. Simultaneously, the four variables contributed 19.1% to the Fitness of National Police officers in the Central Java Regional Police, with an F-value of 10.736 and a p-value of 0.00.  There is a relationship between Body Mass Index, Stress Level, Physical Activity, and the Fitness Level of National Police Officers in the Central Java Regional Police.